Travelers' Diarrhea in Thailand: A Quantitative Analysis Using TaqMan® Array Card. (17th January 2018) - Lertsethtakarn, Paphavee; Silapong, Sasikorn; Sakpaisal, Pimmada; Serichantalergs, Oralak; Ruamsap, Nattaya; Lurchachaiwong, Woradee; Anuras, Sinn; Platts-Mills, James A; Liu, Jie; Houpt, Eric R; Bodhidatta, Ladaporn; Swierczewski, Brett E; et al.
Abstract : The TaqMan® array card (TAC) was used to detect enteropathogens in stool samples from travelers' diarrhea cases and asymptomatic controls in a hospital-based surveillance in Thailand. Analyses were performed to determine pathogen–disease association to compare TAC and conventional results. Abstract: Background: Travelers' diarrhea (TD) is a common illness experienced by travelers from developed countries who visit developing countries. Recent questionnaire-based surveillance studies showed that approximately 6%–16% of travelers experienced TD while visiting Thailand; however, a majority of TD information was limited mainly to US military populations. Methods: A TD surveillance study was conducted at Bumrungrad International Hospital in 2012–2014 in Bangkok, Thailand. Enteropathogens were identified using conventional methods and the TaqMan® array card (TAC), which uses real-time polymerase chain reaction for the simultaneous detection of multiple pathogens. Analyses to determine pathogen–disease and symptoms association were performed to elucidate the clinical relevance of each enteropathogen. Results: TAC identified more pathogens per sample than conventional methods. Campylobacter spp. were the most prevalent, followed by the diarrheagenic Escherichia coli and norovirus GII. These agents had significant pathogen–disease associations as well as high attributable fractions among diarrheal cases. A wide range of pathogen loads for Campylobacter spp. was associated with TD, while heat-labile toxin enterotoxigenic Escherichia coli was associated with an increased pathogen load. Most cases were associated with inflammatory diarrhea, while Campylobacter spp. and Shigella spp. were associated with dysentery. Conclusions: A pan-molecular diagnostic method such as TAC produces quantifiable and comparable results of all tested pathogens, thereby reducing the variability associated with multiple conventional methods. This allows better determination of the clinical relevance of each diarrhea etiologic agent, as well as their geographical relevance in Thailand.